2020
DOI: 10.1109/access.2020.2978008
|View full text |Cite
|
Sign up to set email alerts
|

Formation Control of Multi Unmanned Aerial Vehicle Systems Based on DDS Middleware

Abstract: In this paper formation control of Unmanned Aerial Vehicle System (UAVs) is introduced. L 1 controller with potential field technique and Data Distribution Service (DDS) middleware used for the navigation of the agents, which is multi-UAVs. L1 adaptive controller used to stabilizing the general equations of motion of each UAVs and the potential field technique used to formalize the followers around the leader. The exchanging data between the leader and the followers done through publisher/subscriber DDS middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To rectify this problem, adaptive control scheme was proposed by adding a linear filter in the whole control structure 19 . This technique was studied further in 20 for the collaborative UAVs. Note that this scheme doesn’t guarantee the estimate parameters to converge to the actual value of the unknown parameters as it was tuned for the worst-case condition.…”
Section: Related Work and Main Contributionsmentioning
confidence: 99%
“…To rectify this problem, adaptive control scheme was proposed by adding a linear filter in the whole control structure 19 . This technique was studied further in 20 for the collaborative UAVs. Note that this scheme doesn’t guarantee the estimate parameters to converge to the actual value of the unknown parameters as it was tuned for the worst-case condition.…”
Section: Related Work and Main Contributionsmentioning
confidence: 99%
“…They concluded that the proposed distributed control algorithm is more efficient than a single UAV system. The added advantage of utilizing DDS middleware for communication between multiple UAV systems are presented and discussed in [93], [94].…”
Section: Dronesmentioning
confidence: 99%
“…If G's rank is less than Q's dimensions, then Equation ( 8) is under-actuated. A detailed quadrotor dynamic is available in [8,9,25].…”
Section: Dynamics Of Quadrotormentioning
confidence: 99%
“…DDS middleware has been proposed and designed to overcome the issue of the data loss between multiple UAVs, as well as the interoperability issue associated with heterogeneous systems. Therefore, application of the DDS middleware technique augmented with the flocking approach resulted in significant improvements in flexibility, reliability, and portability [8,9].…”
Section: Introduction 1motivationmentioning
confidence: 99%